2022
DOI: 10.1093/rpd/ncac074
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Regional Diagnostic Reference Levels in Adult Computed Tomography for Four African Countries: A Preliminary Survey

Abstract: This preliminary study aims towards the establishment of regional diagnostic reference levels (DRLs) for routine adult computed tomography (CT) examinations. The study was performed on 54 CT facilities from four African countries (Ghana, Kenya, Namibia and Senegal) and the results compared with international DRLs. Data were collected from facilities using a structured questionnaire provided by the International Atomic Energy Agency. Dose descriptors (volume computed tomography dose index [CTDIvol] and dose len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…This suggests that most of the installation of CT scan across the public and private hospital have been made in recent years. Similar observation were made by 7 who suggested that the number of CT scanners in direct medical use in Kenya increased by over 80 % in the past decade (2012-2019). The overall increase in the number of CT scans between 2016 and 2018 can, to a large extent, be attributed to the MES, a public-private partnership project (PPP) introduced in 2016, that has equally resulted in availability of more imaging modalities in the public sector.…”
Section: Resultssupporting
confidence: 79%
“…This suggests that most of the installation of CT scan across the public and private hospital have been made in recent years. Similar observation were made by 7 who suggested that the number of CT scanners in direct medical use in Kenya increased by over 80 % in the past decade (2012-2019). The overall increase in the number of CT scans between 2016 and 2018 can, to a large extent, be attributed to the MES, a public-private partnership project (PPP) introduced in 2016, that has equally resulted in availability of more imaging modalities in the public sector.…”
Section: Resultssupporting
confidence: 79%
“…IAEA and African experts established the first harmonized imaging quality control protocols for Africa in 2020 to help achieve a minimum standard throughout the region [ 22 ]. An initial study on regional diagnostic reference levels for computed tomography included data from Ghana, Kenya, Namibia, and Senegal [ 23 ] indicating that regional collaboration is expanding. Results of studies like these may eventually trickle down into national regulations or similar.…”
Section: Science Diplomacy Actions In Medical Physics Across the Cont...mentioning
confidence: 99%